Numerical heat performance of TiO2/Glycerin under nanoparticles aggregation and nonlinear radiative heat flux in dilating/squeezing channel. (January 2023) - Adnan; Abdulkhaliq M Alharbi, Khalid; Bani-Fwaz, Mutasem Z.; Eldin, Sayed M.; Yassen, Mansour F.
Abstract: Applications: Newly developed fluids termed as "Nanofluids" and their study in dilating/squeezing channel cannot be disregarded. Such flows under various physical constraints are important for purification purposes and other industrial applications. Purpose: and Methodology: This work comprises the modeling and heat transmission ability of TiO2 /G inside a dilating/squeezing channel. The conventional model upgraded including the aggregation effects of nanoparticles and directed nonlinear thermal radiations. The resultant model examined through numerical scheme for actual understanding the heat transport phenomena inside the channel. Major findings: The results reveal that high viscosity parameter ( R 1 = 0.5, 1.0, 1.5, 2.0 ), porous absorber walls and strong surface-surface interaction due to aggregation of nanoparticles significantly control the fluid movement. The pores at the surface ( A 1 = 0.1, 0.3, 0.5, 0.7 ) attract the fluid particles and strong frictional forces between them resists the motion and is rapid for aggregated nanofluid. Further, thermal radiations ( R d = 1.0, 1.5, 2.0, 2.5 ) produce considerable heat which can be used to breakdown the aggregation between the nanoparticles.